Dispute resolution in relation to delay of construction project - Soon, Tan Kian (2010)
Time has been a major constraint in the project undertaking in Malaysia. Hence, proper works scheduling need to be planned. However, there are always unexpected circumstances out of parties? control for the project processes slipping over its planned schedule and end-up with disputes on delay issues. Usually, people always look for more economical and time saving method for dispute settlement. But there are still a portion of people choose to settle via litigation proceeding. This problem brought to this study which aims to investigate the origin of disputes settlement via litigation proceeding that contributed by delay in project undertaking. The objectives of the study include the analysis of taxonomy of delay and review of the available dispute resolution techniques. Analysis on the trend of delay dispute resolution by litigation in the selected cases is made. Third objective was set where the outline for dispute avoidance is formulated. This study is restricted to the cases within Malaysia. Analysis shows that the main causes of the delay are the mostly defaulted by the proprietor; the executors were showed as the majority party in filing the court suit among which they obtained high percentage in winning the award. The study shows that delay dispute settlement via litigation proceeding generally occurred when the financial conflict between parties take place. In order to avoid the settlement of dispute via litigation, measures of dispute avoidance are proposed. The findings are expected to be useful as further references for parties in facilitate the execution of their construction work.